ANALISIS PENERIMAAN PAJAK REKLAME JAKARTA BARAT DILIHAT DARI PENGARUH PDRB DAN TINGKAT INFLASI - Sukriyanto Sukriyanto (Jurnal Akuntansi Bisnis, 2017)
The researcher chooses tax billboard as the topic because tax billboard is one of local taxes that contributes large enough to Original Income area. This research aims to identify the factors that affect tax revenue Billboard that would later be used as the basis for the Government to set up the plan of tax revenue Billboard. The research method used is a quantitative method of associative with the help of IBM SPSS Statistics software 20 with regression analysis. Researcher also ensures that the data used has survived the test of classical assumptions. The conclusion uses t-test and F-test of regression test.The result of the test t find that Income Gross Area (GDP) have links to positive and very powerful as well as affect tax revenue significantly Billboard, while the inflation rate had a negative relationship is very weak and does not affect tax revenue significantly Billboard. However, both of these variables simultaneously affecting tax revenue significantly Billboard.On the basis of the research that has been done, the researcher recommends that local authorities consider GDP at territory in setting target tax revenue plan/Billboard. Because of the company's production value describes the GDP in certain regions, a conducive condition must also be prepared by passing Government policies and regulations are issued so that the company can conduct operations properly. Inflation rate is generally worth noting, but not a priority.Keywords: advertisement , regional gross revenue , rate of inflation